Boson-boson effective nonrelativistic potential for higher-derivative electromagnetic theories in D dimensions - Accioly, Antonio [UNESP]; Dias, Marco [UNESP] (American Physical Society (APS), 2004)
The problem of computing the effective nonrelativistic potential U D for the interaction of charged-scalar bosons, within the context of D-dimensional electromagnetism with a cutoff, is reduced to quadratures. It is shown that U3 cannot bind a pair of identical charged-scalar bosons; nevertheless, numerical calculations indicate that boson-boson bound states do exist in the framework of three-dimensional higher-derivative electromagnetism augmented by a topological Chern-Simons term.